An exploratory investigation of crossflow microfiltration for solid/liquid separation in biological wastewater treatment - Bailey, Andrew Douglas (Department of Chemical Engineering, 2016)
This thesis contains the results and discussion of an exploratory investigation into the application of Crossflow Microfiltration (CFMF) for solid/liquid separation in biological wastewater treatment systems. The principal objective of the study was to assess the influence of CFMF on the performance of identified biological wastewater treatment systems. It was not the objective to optimise filtration performance. A literature review indicated that the crossflow mode of filtration has been widely accepted as a unit operation in the fermentation industry. The filtration mode is now being applied not only for solid/liquid separation but also for separations on a molecular and ionic level. Very few applications of crossflow filtration in the context of biological wastewater treatment solid/liquid separation are reported in the literature. The reasons for this limited experience would appear to be the scale involved and the perceived high costs; separations in the fermentation industry are usually conducted at relatively small scale (laboratory or pilot-scale) and involve high-value products, justifying high capital and operating costs. Also, the high level of separation performance attained is perhaps not necessary for many wastewater treatment applications. No doubt these reservations are largely valid. However, these arguments cannot be applied equally to all filtration methods and wastewater treatment schemes. For example, the costs of microfiltration are substantially less than ultrafiltration or reverse osmosis, and in certain cases effluents with extremely low suspended solids contents may be required. In the light of these observations an investigation of CFMF for solid/liquid separation in biological wastewater treatment systems appears justified. Two biological treatment systems were selected for study: the Upflow Anaerobic Sludge Bed (UASB) reactor and the Activated Sludge system. The envisaged benefits accruing from the application of CFMF were different in each case.